Livable Cities for the 21st Century : The Post Habitat II Agenda for the World Bank - Wolfensohn, James D. (World Bank, Washington, DC, 2017)
Habitat II, the second United Nations conference on human settlements, also known as the “City Summit,” concluded its work on June 14, 1996, in Istanbul. Habitat II indelibly marked the increasingly urban nature of the world and the urgency, extent, and increasing size of problems facing people in cities, especially the poor. The conference developed consensus around the need to achieve sustainable development in urban areas, with special emphasis on the provision of basic services and shelter for the poor. The summit underscored the role of partnerships. Mr. Wolfensohn noted that partnerships are one of the key thrusts of all the work at the World Bank. The Bank has a long history with the urban sector. Looking to the future, the Bank identified three key priorities for action to make cities livable today: bringing basic services to the poor; a healthier urban environment; and finance for people in cities. The Bank made important commitments at Istanbul to increase its support to urban development, particularly through people-centered approaches.